2001
DOI: 10.1034/j.1399-0004.2001.590609.x
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic duplication of 21q in an individual with a clinical diagnosis of Down syndrome

Abstract: We describe an adult male who was diagnosed with Down syndrome (DS) at 9 months of age, but had repeatedly normal karyotypes until recent mid-resolution chromosome studies showed a possible duplication of 21q22.13 to 21q22.3. The abnormality was investigated using fluorescent in situ hybridization (FISH) studies. These showed hybridization of a whole chromosome paint probe (wcp21, Oncor Coatasome 21) to the entire length of both chromosome 21 homologues and one very large hybridization signal of a cosmid conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…To date, at least 39 cases of Down syndrome with pure partial tirsomy 21 have been reported [24,25], but the prenatal diagnosis of pure partial trisomy 21q associated with Down syndrome is quite rare. Lee et al, [26] reported a case of prenatal diagnosis of pure trisomy 21q(21q13 → q22.2) due to an unbalanced cryptic insertion (4;21)(q21;q22.1q22.3) inherited from the carrier father.…”
Section: Discussionmentioning
confidence: 99%
“…To date, at least 39 cases of Down syndrome with pure partial tirsomy 21 have been reported [24,25], but the prenatal diagnosis of pure partial trisomy 21q associated with Down syndrome is quite rare. Lee et al, [26] reported a case of prenatal diagnosis of pure trisomy 21q(21q13 → q22.2) due to an unbalanced cryptic insertion (4;21)(q21;q22.1q22.3) inherited from the carrier father.…”
Section: Discussionmentioning
confidence: 99%
“…As an explanation for absence of trisomy 21 in different tissues of patients with apparent manifestations of the syndrome, several suggestions were proposed: (1) low-level mosaicism, (2) the presence of the trisomic cell line in tissues other than those investigated, (3) elimination of the aberrant cell line in vivo or selective regress in vitro [Engel et al, 1970], and (4) gene mutation that might cause a "phenocopy" [Hall, 1962]. Subsequent studies showed the presence of a cryptic duplication of the Down syndrome critical region in individuals with clinical diagnosis of Down syndrome and an apparently normal karyotype [see for reference Forster-Gibson et al, 2001]. However several patients with mental retardation and Down syndrome phenotype, but without molecularly detectable duplication of the critical region, have been reported [McCormick et al, 1989;Ahlbom et al, 1996].…”
Section: Sex Ratio In False Positive Diagnosismentioning
confidence: 99%
“…In comparison with STRs, SNPs are more numerous and can better define the DSCR. Analysis of STRs in the DSCR should also detect partial trisomies (6 ), but to our knowledge, examples have not been reported, and discovery of partial duplication in chromosome 21 relies essentially on FISH technology (20 ). SNPs are the most abundant polymorphisms in the human genome with one SNP occurring each kilobase on average (13 ).…”
Section: Discussionmentioning
confidence: 99%